Associations between Manual Abilities, Gross Motor Function, Epilepsy, and Mental Capacity in Children with Cerebral Palsy - GAJEWSKA*, Ewa; SOBIESKA, Magdalena; SAMBORSKI, WÅ‚odzimierz (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Gajewska E, Sobieska M, Samborski W. Associations between Manual Abilities, Gross Motor Function, Epilepsy, and Mental Capacity in Children with Cerebral Palsy. Iran J Child Neurol. 2014 Spring 8(2):45-52. Objective This study aimed to evaluate gross motor function and hand function in children with cerebral palsy to explore their association with epilepsy and mental capacity. Material & Methods The research investigating the association between gross and fine motor function and the presence of epilepsy and/or mental impairment was conducted on a group of 83 children (45 girls, 38 boys). Among them, 41 were diagnosed with quadriplegia, 14 hemiplegia, 18 diplegia, 7 mixed form, and 3 athetosis. A neurologist assessed each child in terms of possible epilepsy and confirmed diagnosis in 35 children. A psychologist assessed the mental level (according to Wechsler) and found 13 children within intellectual norm, 3 children with mild mental impairment, 18 with moderate, 27 with severe, and 22 with profound. Children were then classified based on Gross Motor Function Classification System and Manual Ability Classification Scale. Results The gross motor function and manual performance were analysed in relation to mental impairment and the presence of epilepsy. Epilepsy was found to disturb conscious motor functions, but also higher degree of mental impairment was observed in children with epilepsy. Conclusion The occurrence of epilepsy in children with cerebral palsy is associated with worse manual function. The occurrence of epilepsy is associated with limitations in conscious motor functions. There is an association between epilepsy in children with cerebral palsy and the degree of mental impairment. The occurrence of epilepsy, mainly in children with hemiplegia and diplegia is associated with worse mental capacities. References Richards CL, Malouin F. Cerebral palsy: definition, assessment and rehabilitation. Handb Clin Neurol 2013;111:183-95. Sellier E, Uldall P, Calado E, Sigurdardottir S, Torrioli MG, Platt MJ, et al. Epilepsy and cerebral palsy: characteristics and trends in children born in 1976-1998. Eur J Paediatr Neurol 2012;16(1):48-55. Wallace SJ. Epilepsy in cerebral palsy. Dev Med Child Neurology 2001;43(10):713-7. Bax MCO. Cerebral palsy. In: Aicardi J, editor. Disease of the nervous system in childhood. 2nd ed. London: Mc Keith Press; 1998. p. 210-39. Reid A, Imrie H, Brouwer E, Clutton S, Evans J, Russell D, et al. “If I knew then what I know now”: parents’ reflections on raising a child with cerebral palsy. Phys Occup Ther Pediatr 2011;31(2):169-83. Rosenbaum P, Paneth N, Leviton A, Goldstein M, Bax M, Damiano D, et al. A report: the definition and classification of cerebral palsy April 2006. Dev Med Child Neurology 2007;109:8-14. Palisano R, Rosenbaum P, Bartlett D, Livingston M. Content validity of the expanded and revised Gross Motor Function Classification System. Dev Med Child Neurology 2008;50(10):744-50. Öhrvall AM, Eliasson AC. Parents and therapists perceptions about the content and construct of Manual Ability Classification System, MACS. Scand J Occup Ther 2010;17(3):209-16. Marszał E.Występowanie, diagnostyka i leczenie padaczki u dzieci z mózgowym porażeniem dziecięcym. Neurologia dziecięca;2006:15, 30:65-8. Blair E, Watson L. Epidemiology of cerebral palsy. Semin Fetal Neonatal Medicine 2006;11(2):117-25. Meberg A, Broch H. Etiology of cerebral palsy. J Perinat Med 2004;32(5):434-9. Blair E. Epidemiology of the cerebral palsies. Orthop Clin North Am 2010;41(4):441-55. Hellbrűge T, Fritz L, Menara D, Schamberger R, Rautenstrauch T. Monachijska Funkcjonalna Diagnostyka Rozwojowa. Kraków: Antykwa; 1994. p. 80-130. Arnould C, Penta M, Renders A, Thonnard JL. Abilhand-Kids: a measure of manual ability in children with cerebral palsy. Neurology 2004;63(6):1045-52. Carnahan KD, Arner M, Hägglund G. Association between gross motor function (GMFCS) and manual ability (MACS) in children with cerebral palsy. A population-based study of 359 children. BMC Musculoskeletal Disorders 2007;21:50. Bax MC, Keith Brown J. The spectrum of disorders known as CP. In: Scrutton D, Damiano D, Mayston M, editors. Management of the Motor Disorders of Children with CP. Clinics in Developmental Medicine London: Mac Keith Press; 2004. p. 83-140. Kwong KL, Wong SN, So KT. Epilepsy in children with cerebral palsy. Pediatr Neurol 1998 ;19:31-6. Odding E, Roebroeck ME, Stam HJ. The epidemiology of cerebral palsy: incidence, impairments and risk factors. Disabil Rehabil 2006;28(4):183-91. Sugiura C, Shiota M, Ieshima A, Ohno K. [Epilepsy in patients with cerebral palsy–analysis of frequency and clinical prognosis]. No To Hattatsu 2003;35(6):478-83. McLellan A. Epilepsy – an additional risk factor for psychological problems in cerebral palsy. Dev Med Child Neurology 2008;50(10):727. Kulak W, Sobaniec W, Smigielska-Kuzia J, Kubas B, Walecki J. A comparison of spastic diplegic and tetraplegic cerebral palsy. Pediatr Neurol 2005;32(5):311-7. Rossman BS, Ashwal S. Evaluation of the child with cerebral palsy. Seminars in Pediatr Neurol 2004;11(1):47-57.